Specificity tuning of antibody fragments to neutralize two human chemokines with a single agent - Fagète, Séverine (Landes Bioscience, 2009)
Chemokines are important mediators of the immune response that are responsible for the trafficking of immune cells between lymphoid organs and migration towards sites of inflammation. Using phage display selection and a functional screening approach, we have isolated a panel of single-chain fragment variable (scFv) capable of neutralizing the activity of the human chemokine CXCL10 (hCXCL10). One of the isolated scFv was weakly cross-reactive against another human chemokine CXCL9, but was unable to block its biological activity. We diversified the complementarity determining region 3 (CDR3) of the light chain variable domain (VL) of this scFv and combined phage display with high throughput antibody array screening to identify variants capable of neutralizing both chemokines. Using this approach it is therefore possible to engineer pan-specific antibodies that could prove very useful to antagonize redundant signaling pathways such as the chemokine signaling network.